A comparison of the alterations of oral microbiome with fixed orthodontic therapy and clear aligners: a systematic review - Alessandra Lucchese; Marta Marcolina; Nicasio Mancini; Roberto Ferrarese; Serena Acconciaioco; Enrico Gherlone; Chiara Bonini; Maurizio Manuelli; Antonella Polimeni (Journal of Oral Microbiology)
Aim The oral microbiome plays a fundamental role in maintaining homeostasis of the oral cavity. In the last decade there has been an increasing use of clear aligners, which guarantee aesthetics and comfort for the patient. The aim of this work is to conduct a systematic review regarding the alterations in bacterial flora and oral health with aligner and fixed orthodontic therapy.Design A systematic review was conducted following the PRISMA Statement. Using the search strategy “(clear aligners OR Invisalign) AND (fixed therapy OR fixed orthodont * therapy) NOT (thermoplastic retainers) AND (oral microbiome OR oral microbiota * OR oral microbiology * OR oral health)”, in the main scientific databases. Two scales were applied to assess the quality of scientific evidence: ROBINS-I and RoB 2.Results A total of 484 articles emerged of which 9 met our inclusion/exclusion criteria. Afterwards the application of the rating scales, 1 article was found to be at low risk of bias, 6 at moderate and 2 at serious risk of bias.Conclusion Both therapies cause an alteration of the oral microbiome, but the changes induced by the aligners seem to be compatible with a better oral health compared to fixed appliances.